2008
DOI: 10.1094/phyto-98-3-0353
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Resistance to Wheat Leaf Rust, Stem Rust, and Powdery Mildew in Aegilops sharonensis

Abstract: Aegilops sharonensis (Sharon goatgrass) is a wild relative of wheat and a rich source of genetic diversity for disease resistance. The objectives of this study were to determine the genetic basis of leaf rust, stem rust, and powdery mildew resistance in A. sharonensis and also the allelic relationships between genes controlling resistance to each disease. Progeny from crosses between resistant and susceptible accessions were evaluated for their disease reaction at the seedling and/or adult plant stage to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…A substantial contribution to reducing losses could be obtained if multiple independent R genes were cloned, shown to recognize distinct and relatively immutable and indispensable pathogen effectors, and transformed in a stack into an elite variety. Several groups around the world are now collaborating to achieve this goal, starting with resistance genes to Ug99 defined in wild relatives of wheat from the Sitopsis section of the Aegilops genus, such as Aegilops sharonensis [24,25] (). As genomics methods continue to be refined, and as knowledge of the genomes of crops and their relatives continues to expand, resistance gene isolation will get easier.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial contribution to reducing losses could be obtained if multiple independent R genes were cloned, shown to recognize distinct and relatively immutable and indispensable pathogen effectors, and transformed in a stack into an elite variety. Several groups around the world are now collaborating to achieve this goal, starting with resistance genes to Ug99 defined in wild relatives of wheat from the Sitopsis section of the Aegilops genus, such as Aegilops sharonensis [24,25] (). As genomics methods continue to be refined, and as knowledge of the genomes of crops and their relatives continues to expand, resistance gene isolation will get easier.…”
Section: Discussionmentioning
confidence: 99%
“…In an inheritance study of several Ae. sharonensis accessions to leaf rust, stem rust, and powdery mildew, Olivera et al (2008) detected dominant resistance alleles at genes with major effects. In individual accessions from different geographic regions, the authors found different genes that were effective against all of the P. triticina races evaluated.…”
Section: Resistance To Biotic Stressmentioning
confidence: 95%
“…sharonensis is great, as Olivera et al (2007) recently identified many accessions with resistance to the important wheat diseases of leaf rust, stem rust, stripe rust, powdery mildew, spot blotch, and tan spot. In another recent study, Olivera et al (2008) determined the genetic basis of resistance to wheat leaf rust, stem rust, and powdery mildew in Ae. sharonensis.…”
Section: Introductionmentioning
confidence: 99%